2016
DOI: 10.1021/jacs.6b07066
|View full text |Cite
|
Sign up to set email alerts
|

Well-Defined Cobalt(I) Dihydrogen Catalyst: Experimental Evidence for a Co(I)/Co(III) Redox Process in Olefin Hydrogenation

Abstract: The synthesis of a cobalt dihydrogen Co(I)-(H2) complex prepared from a Co(I)-(N2) precursor supported by a monoanionic pincer bis(carbene) ligand, (Mes)CCC ((Mes)CCC = bis(mesityl-benzimidazol-2-ylidene)phenyl), is described. This species is capable of H2/D2 scrambling and hydrogenating alkenes at room temperature. Stoichiometric addition of HCl to the Co(I)-(N2) cleanly affords the Co(III) hydridochloride complex, which, upon the addition of Cp2ZrHCl, evolves hydrogen gas and regenerates the Co(I)-(N2) compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
150
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(160 citation statements)
references
References 55 publications
10
150
0
Order By: Relevance
“…Later, Milstein and co‐workers have developed another Co II system with pyridine‐based PNN pincer ligand for the hydrogenation of esters and nitriles . Very recently, the group of Fout has showed that Co I complexes with monoanionic bis(carbene) ligands can also promote olefin hydrogenation through a Co I /Co III redox cycle (Figure ) …”
Section: Figurementioning
confidence: 99%
“…Later, Milstein and co‐workers have developed another Co II system with pyridine‐based PNN pincer ligand for the hydrogenation of esters and nitriles . Very recently, the group of Fout has showed that Co I complexes with monoanionic bis(carbene) ligands can also promote olefin hydrogenation through a Co I /Co III redox cycle (Figure ) …”
Section: Figurementioning
confidence: 99%
“…Recently, the groups of Kempe and Kirchner used PNP pincer cobalt and iron complexes for selective hydrogenations of polar bonds with high tolerance of other unsaturated bonds . Moreover, effective cobalt catalysts based on NNP, PBP, and CCC pincers have been reported …”
Section: Introductionmentioning
confidence: 99%
“…The catalytic activity of ( Mes CCC)CoI(N 2 )(PPh 3 ) 6a was tested in the reduction of styrene at room temperature. [27] At the end of the reaction( 2h), the dihydrogens pecies 6b was detected as ar estings tate of the catalytic cycle. This is probably the first case in which aw ell-definedh omogeneous cobalt-dihydrogen complexh as been used as an effective hydrogenation catalyst.…”
Section: Catalytic Reduction 21 Catalytic Hydrogenationmentioning
confidence: 98%
“…The catalytic activity of ( Mes CCC)CoI(N 2 )(PPh 3 ) 6 a was tested in the reduction of styrene at room temperature . At the end of the reaction (2 h), the dihydrogen species 6 b was detected as a resting state of the catalytic cycle.…”
Section: Catalytic Reductionmentioning
confidence: 99%